1982
DOI: 10.1002/app.1982.070270316
|View full text |Cite
|
Sign up to set email alerts
|

The use of extensional rheometry to establish operating parameters for stretching processes

Abstract: This work describes a method of determining the limits of uniform extensibility, in terms of failure and fracture, from rheological tests in extensional flow. The limit of uniform stretching can be expressed in terms of the Weissenberg number for the process, as demonstrated by data for three chemically diverse polymers, polystyrene, poly(methyl methacrylate), and a polyester. The BKZ‐K model can be used to predict necking failure, as determined by the Considére criterion, and an empirical correlation can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…7. As can be seen, despite a relatively large experimental scatter, the general trend is of increasing values for the strain at maximum axial force, with increasing We, which is in general agreement with previous observations by other authors [32,35,36]. However, there seems to be a lower dependency of strain at failure on We for PE-D, i.e., the copolymer with the broader dispersion of molecular weight.…”
Section: Failure Behaviorsupporting
confidence: 90%
See 1 more Smart Citation
“…7. As can be seen, despite a relatively large experimental scatter, the general trend is of increasing values for the strain at maximum axial force, with increasing We, which is in general agreement with previous observations by other authors [32,35,36]. However, there seems to be a lower dependency of strain at failure on We for PE-D, i.e., the copolymer with the broader dispersion of molecular weight.…”
Section: Failure Behaviorsupporting
confidence: 90%
“…One criterion for failure (necking) that was first applied and used for solids is the Considère criterion [34]. This criterion predicts the beginning of necking to occur when a maximum is observed in the force-extension curve, and other authors have used this simple criterion to discuss failure for different stretching conditions (see, for example, Pearson and Connelly [35] and McKinley and Hassager [36]). However, Joshi and Denn [33] recently showed that this criterion is not directly applicable when there is a substantial viscous component to the flow, and that its applicability is likely to be limited only to situations in which high Weissenberg numbers are found.…”
Section: Failure Behaviormentioning
confidence: 99%
“…This also occurred due to the lower elongational viscosity as investigated by Yao et al (1998Yao et al ( , 2000. However, our results of the temperature and strain rate dependence of Hencky strains at ductile failure do not agree with the experimental results of White (1977, 1978) and the simulation of Hassager et al (1998), but are consistent with the experimental and simulation results of Pearson and Connelly (1982).…”
Section: Discussioncontrasting
confidence: 60%
“…On the other hand, the other materials referred above did not show any marked dependence with the strain rate. Pearson and Connelly [11] have also performed experiments in extension with PS, PMMA and POCH (a co-polyester), and found that the Hencky strain to break was also almost independent of strain rate.…”
Section: Introductionmentioning
confidence: 94%